Draft Genome Sequence of a Glutaminase production bacterium, Bacillus sp.B12, Isolated from Diyala Soil - Alqaysi, 1Rana Hussein Naser; Aakool, Israa Tareq; Abdelhameed, Alyaa (International Journal of Psychosocial Rehabilitation, 2020)
Thirteen environmental isolate were isolated from soil from Diyala city, Iraq. The isolates were identified using phenotypic characteristic methods. All isolates were Gram-positive, spore-forming, motile, aerobic growth. The strians were tested for L-glutaminase production, apromising isolate, B12 presented the highest L-glutaminase activity. Taxonomic position for the selected bacterium (B12)was investigated on the basis of whole genome sequencing(WGS). Comparative computer database analyses revealed that the bacterium is Bacillus sp.B12 (Genbank accession number: SAMN12069785). In prediction of silico for antimicrobial and metal-resistance of Bacillus sp. B12, by RAST tool.Many toxicity resistance and secondary metabolite genes were detected.In vitrothe selected isolate was optimized formaximum tolerance concentrations (MTC) for four metal salts: barium chloride (BaCl2), cadmiumsulfate (CdSO4), ferric sulfate (FeSO4), nickel sulfate (NiSO4), and zinc sulfate (ZnSO4)in the 0-10 mM range.Bacillus sp.B12could tolerate 10mM of Ba2+, and up to 6 mM of Zn2+.The optimal inoculum size was 1.8×104 cell/ml that produced the highest L-glutaminase activity (4.22 U/ml).The enzyme maximum activity was accomplished 120u/min when the enzyme was incubated with 200 mM of glutamine at pH7.5 under 35ºC for 20 hrs. by using an incubation period of 20 hrs the maximal GLUase production wasachieved, with an optimum of pH 7.5, a temperature of 35 ⁰C for incubation, an agitation rate of 120 rpm. which produce a glutaminase and for further use of pharmaceutical use may be potential candidate.